An Effective Power Dispatch Strategy for Clustered Microgrids While Implementing Optimal Energy Management and Power Sharing Control Using Power Line Communication - Ahmed Mohamed, Ahmed Haidar; Adila, Fakhar; Kashem M., Muttaqi (IEEE, 2020)
The mitigation of uncertainty in the availability ofpower generation from microgrids to enable renewable resourcesto be dispatched is a daunting task for the individual operators. In-stalling energy storage systems may reduce the impact of renewableenergy intermittency. However, a peculiarity in energy manage-ment can be arisen, particularly, when different energy providersmanage these resources. Hence, an intelligent utilization approachshould be devised to maximize the benefits of using battery energystorage, since the cost of this system is the most expensive part. Thisarticle proposes an effective power dispatch strategy for clusteredmicrogrids. The developed hybrid algorithm implements optimalenergy management and power sharing control using binary data.The frequency-shift keying (FSK) technique has been adoptedfor transmitting the binary signal over the power line commu-nication (PLC). A part of the algorithm is utilized to deal withthe optimal scheduling control, whereas the other actuates thedynamic-demand-response-based photovoltaic power forecasting.The performance of the proposed approach with the formulatedbackup injection index has been validated using data collectedfrom the practical network of “Bario, Sarawak.” The presentedresults suggest that the implementation of the proposed strategy canimprove the efficiency of the overall system, causing less operatingcost and fast return. It was also found that the binary signal can betransferred with less distortion through PLC networks when usingthe FSK technique compared to other techniques.